16 The cardiac toxicity CMR study in patients with lung cancer treated with chemo-radiotherapy: The cart study- a semi quantitative analysis of the myocardial perfusion index. (18th April 2016) - Mangion, K; Berry, C; Foster, J; Nowicki, S; Sattar, N; O'Rourke, N; Glegg, M; Sankaralingham, M; Paul, J; Lawless, C; Stobo, J; Mohammed, N; et al.
Abstract : Background: There are limited data on the cardiac effects of radiotherapy and chemo-radiotherapy on the heart in patients with non-small cell lung cancer (NSCLC). CART is a pilot study designed to investigate change in myocardial function and tissue properties where Patients will undergo cardiac magnetic resonance (CMR) at baseline, during treatment, at 6 weeks and at 6 months after treatment completion. Here we report our preliminary findings related to temporal changes in myocardial perfusion index (MPI). Methods: CMR was performed on a Siemens MAGNETOM Verio (Erlangen, Germany) 3.0 Tesla scanner. First-pass myocardial perfusion was assessed by saturation recovery prepared dynamic contrast enhanced sequence during administration of 0.1 mmol/kg of gadoterate meglumine (Dotarem). Semiquantitative analysis was performed on segmented basal and mid-LV short axis slices to derive normalised upslopes of myocardial signal intensity profiles (myocardial perfusion index, MPI). The change in MPI over time was analysed statistically using a linear mixed effects model. Results: 13 patients currently have undergone CMR at baseline and during treatment (mean age 66 years, SD: 9; 71% male),  8 patients have undergone CMR at 6 weeks post treatment initiation (5 patients lost to follow-up/ died), and 6 patients have undergone CMR at 6 months from baseline (n = 2 lost to follow-up/ died). Perfusion index (Figure 1 ) varies significantly with time (p = 0.0015). After adjustment for multiple testing, the increase from baseline is statistically significant at 6 weeks (p = 0.014) and approaches significance at 6 months (p = 0.074) post treatment. Conclusion: Change in microvascular perfusion is most pronounced 6 weeks following the completion of treatment. This finding will be used in the design of future clinical studies, where measurement of MPI will provide a robust comparison of different existing and emerging treatment protocols for NSCLC with regard to their effects on myocardial physiology. Funding: Beatson Oncology Centre Fund